Ansiedade e estratégias de enfrentamento adotadas pelas mulheres com diagnóstico de câncer de mama em tratamento quimioterápico - Silva, Araceli Vicente da (2015)
Objectives: To identify the trait and state anxiety and psychological coping strategies for patients with breast cancer, and to examine its relationship with sociodemographic and clinical variables, and to correlate the coping strategies adopted with the trait and state anxiety. Methodology: This is a descriptive crosssectional study, developed in the chemotherapy Ylza Bianco outpatient sector of the Hospital Santa Rita, located in Vitória / ES. The sample was randomly taken, and was composed by 307 women with prior breast cancer intravenous chemotherapy, either adjuvant or palliative. Data was collected through interviews, and the Confront Problems Mode Scale (EMEP) and the Anxiety Inventory (A-Trait) and State (State B) – IDATE scales were used. For statistical analysis, the SPSS program, version 19.0, was used. Results: 60.9% of patients were found to have low levels of trait anxiety, and 91.5% low level of the state of anxiety. The coping strategy most used by patients was coping focused on the problem, followed by focus on religion, and the coping strategies focused on social support and emotion were the least used. A significant correlation of trait anxiety and coping strategies focused on the problem (p<0,000); with focus on emotion (p<0,000); state of anxiety with coping focused on the problem (p=0,001 ); and with focus on emotion (p=0,004) was proved. Conclusion: The socio-demographic and clinical variables influence in a direct way in the level of anxiety and choice of coping strategy to be adopted by patients. It was found that the coping strategy chosen by women is directly related to their state and trait anxiety. Providers should know the correlation between coping and anxiety to develop measures to implement and help patients to choose efficient strategies for coping and, as a consequence, reducing the level of anxiety.